The Sequential Levels of the Digital Divide in the Educational Domain Among Indonesian University Students - Umar Halim; Nurul Hidayat (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This research examines the sequential relationships between digital access, digital literacy, digital usage, and educational outcomes in the context of the digital divide in higher education in Indonesia. The study utilizes data from 457 undergraduate students across six urban and rural universities, employing a quantitative survey methodology and applying Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the causal pathways. Findings indicate that access, as assessed by device type and duration, significantly improves digital literacy, which subsequently influences educational technology usage patterns and learning outcomes. Communication and content creation skills significantly impact academic performance and satisfaction. The results substantiate a multilevel framework of digital inequality and emphasize the significance of equitable digital engagement beyond simple access. This study provides insights for digital literacy initiatives and educational technology interventions designed to mitigate outcome-based disparities across various geographic and institutional contexts.